Diagnostic journey of a metachronous warthin tumor of the parotid - Dineshkumar Thayalan; Rajkumar Krishnan; PL.Ranganayakidevi S. Palaniappan; Anand Ramanathan (Oral Oncology Reports)
Warthin tumor (WT) accounts for about 20% of all benign salivary tumours and may present as unilateral or bilateral, synchronous or metachronous. Bilateral tumours are more infrequent and occur in 7–10% of the cases. Most of the bilateral tumours are metachronous, with a few cases of synchronous bilateral tumours. Notably, the metachronous occurrence, defined by the development of secondary tumours independently over time, underscores the need for ongoing surveillance and management in salivary gland neoplasms.